2020
DOI: 10.1016/j.clnu.2019.11.024
|View full text |Cite
|
Sign up to set email alerts
|

Critical appraisal of definitions and diagnostic criteria for sarcopenic obesity based on a systematic review

Abstract: Background: Sarcopenic obesity is a clinical and functional condition characterized by the coexistence of excess fat mass and sarcopenia. Currently, different definitions of sarcopenic obesity exist and its diagnostic criteria and cutoffs are not universally established. Therefore, the prevalence and sensitivity of this condition for any disease risk prediction is affected significantly. Aim: This work was conducted under the auspices of the European Society for Clinical Nutrition and Metabolism (ESPEN) and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
206
0
12

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 226 publications
(220 citation statements)
references
References 112 publications
(122 reference statements)
2
206
0
12
Order By: Relevance
“…However, there were some noticeable features. Apart from a very low baseline 25-OHD levels in both groups, applying an obesity cut-off of 27%-30% total body fat, as suggested by the majority of SO-studies [43], found that the vast majority (75%-94%) of our cohort was "osteosarcopenic obese" (SO) [44].…”
Section: Discussionmentioning
confidence: 65%
“…However, there were some noticeable features. Apart from a very low baseline 25-OHD levels in both groups, applying an obesity cut-off of 27%-30% total body fat, as suggested by the majority of SO-studies [43], found that the vast majority (75%-94%) of our cohort was "osteosarcopenic obese" (SO) [44].…”
Section: Discussionmentioning
confidence: 65%
“…Approximately one third of patients were females (33.3%), and median age was 59.0 [49.5–67.9] years. Median disease duration, as estimated by the time from diagnosis to negative swab, was 30 [ [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] ] days. Patient characteristics upon admission to the ED are summarized in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
“…At multivariate analyses only disease duration and - in hospitalised patients - length of stay were significant independent predictors of weight loss, reflecting the importance of disease severity and inflammation to weight loss. In our cohort of COVID-19 patients, weight loss occurred in a relatively short time (median disease duration: 32 [ [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] ] days). This is consistent with previous studies showing that even short periods of bed rest induce marked reductions in muscle protein synthesis resulting in loss of skeletal muscle mass, both in middle-aged and elderly individuals [ [22] , [23] , [24] ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The operational definition of sarcopenic obesity is still under discussion (36) and hence there is no universally accepted classification (24,40,52) . There is a marked heterogeneity in definitions and approaches to diagnose sarcopenic obesity (54) . The threshold values used in previous literature to define both sarcopenia and obesity have varied significantly depending on population, age, sex and ethnicity (55) .…”
Section: Sarcopenic Obesitymentioning
confidence: 99%